The Role of Transformational Leadership and Emotional Intelligence to Increase Innovative Work Behavior with Psychological Empowerment as Mediating Variable - Yan Ari Widodo; Suhana Suhana (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the effect of Transformational Leadership (TL) and Emotional Intelligence (EI) on Innovative Work Behavior (IWB), with Psychological Empowerment (PE) as a mediating variable. This research was conducted on State Civil Apparatus (ASN) in Pekalongan Regency Government. The survey method was used through data from online questionnaires distributed to 350 respondents from 5 Regional Apparatus, namely: Public Works and Spatial Planning Office, Public Housing and Settlement Area and Environment Office, Education and Culture Office, Food Security and Agriculture Office, and Health Office. The sampling technique was carried out using the Percentage Proportional method, which reflects the number of ASNs in each PD. This means that if a sample is taken from 5 PDs, then there must be proportional representation from each PD respondent. Data analysis using the Structural Equation Modeling Partial Least Square (SEM PLS) application with WarpPLS version 7.0 software. Data analysis techniques carried out through several tests, among others: Model Fit Test, Path Coefficients Test, Adjusted R-squared (R²) Test, Multicollinearity Test, Reliability and Validity Test and Mediation Test. The results showed that Transformational Leadership and Emotional Intelligence have a positive effect on Innovative Work Behavior, both directly and partially mediated through Psychological Empowerment as a mediator. This research has theoretical and managerial implications.